Does Scoliosis-Specific Exercise Treatment in Adolescence Alter Adult Quality of Life? - Maciej Płaszewski; Igor Cieśliński; Paweł Kowalski; Aleksandra Truszczyńska; Roman Nowobilski (The Scientific World Journal)
Objective. Health-related quality of life in adults, who in adolescence participated in a scoliosis-specific exercise program, was not previously studied. Design. Cross-sectional study, with retrospective data collection. Material and Methods. Homogenous groups of 68 persons (43 women) aged 30.10 (25–39) years, with mild or moderate scoliosis, and 76 (38 women) able-bodied persons, aged 30.11 (24–38) years, who 16.5 (12–26) years earlier had completed scoliosis-specific exercise or observation regimes, participated. Their respiratory characteristics did not differ from predicted values. The WHOQOL-BREF questionnaire, Oswestry Disability Questionnaire, and pain scale (VAS) were applied. Results. The transformed WHOQOL-BREF scores ranged from 54.6 ± 11.19 in the physical domain in the mild scoliotic subgroup to 77.1 ± 16.05 in the social domain in the able-bodied subgroup. The ODQ values did not generally exceed 5.3 ± 7.53. Inter- and intragroup differences were nonsignificant. Age, marital status, education, and gender were significantly associated with the ODQ scores. Significant association between the ODQ and WHOQOL-BREF social relationships domain scores with the participation in exercise treatment was found. Conclusions. Participants with the history of exercise treatment generally did not differ significantly from their peers who were only under observation. This study cannot conclude that scoliosis-specific exercise treatment in adolescence alters quality of life in adulthood.